Automated MR brain image segmentation and classification using neuro fuzzy - Mohd. Fauzi Othman, author; Shahdan Sudin, author; Mohd. Ariffanan Mohd. Basri, author; The Secong International Conference on Control, Instrumentation and Mechanics Engineering (CIM09)n(2nd : 2009 : Malacca, Malaysia) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL